RUELLIA TUBEROSA LINN. ACTS AS ANTI-FERTILITY AGENT THAT REDUCES SPERM COUNT, MOTILITY AND VIABILITY IN MALE SWISS ALBINO MICE (MUS-MUSCULUS) - H., Pardeshi M.; A., Deshmukh A.; A., Gajare K. (International Journal of Current Pharmaceutical Research, 2016)
Objective: Fertility control is an issue of global public health. Many of the contraceptives available today have one or the other side effects. Many plants and plant products are suggested as contraceptives in folk and traditional systems of medicine. However, that are least exploited in this regard. In the present investigation, root powder of Ruellia tuberosa was studied for its effect on male reproduction in mice. Methods: The Swiss albino mice, Mus musculus of age three months were grouped into four, i)control group, fed on standard pellet, ii)experimental groups I and II received root powder of Ruellia tuberosa 50 mg/mouse/days for 15 d and 30 d respectively in the pellets, iii)positive control groups I and II received cotton seed oil 25 µl/mouse/day for 15 and 30 d and iv)recovery group received Ruellia tuberosa (50 mg/mouse/days) containing pellets for 15 d and later standard pellet for 15 d. Cauda epididymis sperm suspension was analyzed for sperm count, motility and viability. Results: There was a highly significant decrease in sperm count, motility and viability (p<0.001) in experimental groups I and II and positive control groups I and II. The sperm count was reduced to 19.24±1.74 million/ml and 15.97±5.61 million/ml as compared to sperm count in control group (55.12±4.63 million/ml) in experimental groups. Partial reversal of the effect was noticed in a recovery group. Conclusion: The results suggest that Ruellia tuberosa can be a potent member of reversible oral male contraceptives.